Takotsubo cardiomyopathy after cardiac surgery: A case-series and systematic review of literature - Laghlam, Driss; Touboul, Olivier; Herry, Morgane; Estagnasié, Philippe; Dib, Jean-Claude; Baccouche, Mohamed; Brusset, Alain; Nguyen, Lee S.; Squara, Pierre (Frontiers in Cardiovascular Medicine, 2023)
Background Takotsubo cardiomyopathy (TTC) is a rare entity after cardiac surgery. Aims To describe patients’ profile who developed postoperative TTC after cardiac surgery, management, and outcomes. Methods We performed a systematic literature search to extract cases of TTC after adult cardiac surgery (from 1990 to 2021). Additionally, we extracted all cases of TTC in a prospective single-center cohort database of 10,000+ patients (from 2007 to 2019). We then combined all cases in a single cohort to describe its clinical features. Results From 694 screened articles, we retained 71 individual cases published in 20 distinct articles (19 cases reports and 1 case-series). We combined these to 10 cases extracted from our cohort [among 10,682 patients (0.09%)]. Overall, we included 81 cases. Patients were aged 68 ± 10 years-old and 64/81 (79%) were women. Surgery procedures included mitral valve and/or tricuspid valve surgery in 70/81, 86%. TTC was diagnosed in the first days after surgery [median 4 (1–4) days]. Incidence of cardiogenic shock, defined as requirement of vasopressor and/or inotropic support was 24/29, 83% (data available on 29/81 patients). Refractory cardiogenic appeared in 5/81, 6% who required implantation of arterio-venous extra-corporeal membrane oxygenation, and 6/81, 7%, intra-aortic balloon pump. In-hospital mortality was 5/81, 6%. Conclusion This systematic review, based on case reports and case series, showed that postoperative TTC appears as a rare complication after cardiac surgery and mainly occurred after mitral and/or tricuspid valve repair procedures. In this population, TTC is associated with high rate of cardiogenic shock.